Evaluating the Effect of Riddles on Driving. (September 2013) - Emfield, Adam; Leavens, Jennifer; Mouloua, Mustapha; Neider, Mark
While driver distraction has become one of the most studied topics in safety and in human factors, the focus has remained on the traditional elements of driver distraction. In this study, we manipulated the difficulty level of riddles to determine whether the cognitive processing associated with solving them would affect driving performance. Twenty-eight participants completed a series of eighteen short drives while undistracted or listening to a hard or easy riddles. Frequency of pressing the brake pedal, deviation in lane position, and average speed were analyzed. The results indicated that there was a main effect of riddle difficulty on how often the brake pedal was pressed. No main effects of measures on speed maintenance and lane position were found. While these results indicate there may be some differences related to difficulty of solving a problem while driving, further work is required to better quantify the effect.